Accreditation processes of information and documentation degrees in Spain: frameworks and models for improving of teaching quality - Bonal-Zazo, José Luis (2024)
Analysis of the situation of the accreditation of Information and Documentation degrees in Spain. Based on the information available in the Registry of Universities, Centres and Degrees (RUCT) of the Ministry of Universities, a comparative analysis of the situation of accreditation of degrees related to the field of Information and Documentation in Spain is carried out. Based on the data obtained, an assessment is made of the general situation of accreditation in Spanish universities (with special reference to institutional accreditation of centres versus institutional accreditation of degrees); the situation of accreditation of Bachelor's, Master's and PhD degrees in the field of Information and Documentation; and the future prospects for institutional accreditation of these studies. The results show that few Information and Documentation studies are accredited by institutional accreditation (3 Bachelor's degrees, 5 Master's degrees and no doctoral programmes), although both the legislation and the number of existing degrees in the centres make it advisable to opt for institutional accreditation of centres to confirm the official nature of the studies.